Hip and Groin Problems in Female Team-Sport Athletes: A Cross-Sectional Study - Juan Diego Stadelmann; Freddy Reichmann; Romana Franceschini-Brunner; Andrea Mosler; Nicola A. Maffiuletti; Mario Bizzini (International Journal of Sports Physical Therapy)
# Background